Le degré de la maîtrise de l’orthographe d’usage des finalistes du secondaire de la Ville de Mbujimayi (2019-2020). (International Journal of Scientific Research and Management (IJSRM), 2022)
In the Democratic Republic of Congo, the French language remains an official language and the vehicle of teaching at both high school and tertiary education. A great dead of reseachers have drawn a conclusion in their investigations that the learners have difficulties writing the French language even at higher level of the inside educational system. They don’t have the mastery of neither standard spelling nor grammatical spelling. This study is a initical analysis that assesses the high school finalists’ performances and determines their level of the standard spelling of the French language. The latter has but a less effective percent of 56%.